Price Competitiveness of Products on E-Commerce Websites – An Indian Perspective - Singh, Pankaj (Digital Repository of Theses - SSBM Geneva, 2025)
Public accessibility to the internet has significantly changed the world. The worldwide web is now flooded with websites offering information, products and services. E-commerce has become the backbone of global transactions for goods and services initially in developed economies and rapidly growing in the developing economies as well. Initially led by Amazon and eBay, the internet is now a host of millions of e-commerce products and services related websites. India is no exception and as the fastest growing economy backed by a pool of young population, robust network of high-speed mobile and broadband communication, along with rapid urbanization shows immense scope for the growth and competitive environment for e-commerce. Pricing on e-commerce is highly competitive compared to its bricks and mortar peers and Indian market shows extremely cut-throat competition in the e-commerce segment. Studying the price differences among e-commerce sellers at a product level can provide a useful insight on the pricing strategy employed. We have tried to collect the data for different products sold across different e-commerce marketplaces within India to study the price variance and competitive pricing among these online sellers. Keywords – e-commerce, internet, price variance, sellers, India, pricing strategies.